THE EFFECT OF ONLINE LEARNING ON STUDENT LEARNING OUTCOMES AT UPBJJ UT MEDAN - Hernawi Silalahi; Johannes Johannes (SENSEI RESEARCH CENTER, 2021)
The Covid 19 pandemic that has hit parts of the world, has affected and entered the State of Indonesia and changed the social fabric in our country. Education, which initially went well through face-to-face, now has to be done online. This situation requires educators including lecturers to be more responsive to the existing conditions. Students and lecturers who were initially less familiar with the online learning model, Kina had to be